Turkish Drama Serials and Arab Audiences: Why Turkish Serials Are Successful in the Arab World - Berg, Miriam (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
This chapter explores the social and cultural factors that have contributed to the success of Turkish programs in the Arab world. Following the cancelation of Turkish serials on the Arab world’s largest networks in Saudi Arabia and the United Arab Emirates, this chapter will explore how dedicated Arab fans are continuing to watch Turkish shows via alternative platforms after having seen them become such a large part of their daily lives and a permanent fixture on their screens in recent years. By using the Gulf State of Qatar as a departure point, it will examine why Turkish content resonates so closely with female Arab audiences, while also determining their viewing motivations and how Turkish serials have managed to fill a void among its viewers that Arab media has failed to satisfy. At the same time, this chapter will discuss why Turkish dramas have been widely perceived as a women’s genre despite being prime-time serials in Turkey.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice; Qatar (corpus analysé); Qatar (lieu de production du savoir); Turquie (corpus analysé); _Nettoyé